Construction and evaluation of an integrated “Hospital-Community-Family” public cardiopulmonary resuscitation training system - An, Yanhua; Wei, Yun; Wang, Dawei; Ma, Bingchen; Wang, Hua; Cao, Qiumei (Frontiers in Public Health, 2025)
BackgroundEpidemiological investigations have found that 80% of cardiac arrest (CA) events occur in public places or homes. Bystander cardiopulmonary resuscitation (CPR) is the most significant factor for out-of-hospital CA (OHCA) survival. Limited opportunities exist for community residents and family members of patients with chronic diseases to participate in CPR training programs. This study establishes an integrated “Hospital-Community-Family” public CPR training system and assesses its training feasibility.MethodsTraining system construction: the integrated “Hospital-Community-Family” public CPR training system included three levels members and two steps. The three levels members were emergency physicians at level A tertiary hospital, general practitioners (GPs) from community health service centers, and family members of patients with chronic diseases. Two steps included: (1) GPs receiving public CPR training by emergency physicians, passing the examination, and obtaining American Heart Association (AHA) certificate; (2) family members of patients with chronic diseases receiving CPR training from GPs in community health service centers. Training feasibility assessment: a questionnaire survey was used to investigate the CPR knowledge and cognition of family members of chronic disease patients before, after and 6 months after training.ResultsConstruction of the integrated “Hospital-Community-Family” public CPR training system involved eight trainers certified in American Heart Association (AHA) CPR training from the level A tertiary hospital, 23 general practitioners from the community who completed the AHA training and obtained certificates, and 149 family members of patients with chronic diseases under community care who received training. Training feasibility assessment was conducted of family members before, immediately after and 6 months post training, yielding mean scores of 9.83 ± 4.11, 13.97 ± 2.87, and 13.02 ± 3.12 (out of a total score of 17), respectively. The differences were statistically significant (p < 0.001). After 6 months, nearly half of the family members of patients with chronic diseases believed they possessed adequate CPR knowledge and skills and were confident in their CPR abilities.ConclusionsThe proposed integrated “Hospital-Community-Family” public CPR training system demonstrated significant acceptability, practical feasibility, and the necessity for its implementation.